2010
DOI: 10.1021/cm100866g
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Preparation of SnO2 and Pt-Doped SnO2 As Inverse Opal Thin Films for Gas Sensing

Abstract: A new, fast, one-pot synthesis of SnO 2 and Pt-doped SnO 2 inverted opal thin films, to be used as materials for gas sensing, was carried out. Films were built from crystalline cassiterite nanoparticles, uniform in size (∼5 nm), resulting in a well-organized hierarchical structure of macro-and mesopores. The noble metal was homogeneously dispersed into the sensing layer of the oxide and the doping centers were present as Pt(IV) and Pt(II) species, partially reduced to Pt(0) after the interaction with the reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 32 publications
(18 reference statements)
1
66
0
Order By: Relevance
“…This is in agreement with the relatively regular array of WO 3 nanocrystals found in the inverse opal structure (see TEM micrographs, Figure 4a,b) and can be associated with a surface reactivity similar to that described for SnO 2 materials. 23 Differently, Pt-doped WO 3 sensors show β values as always higher than 0.5 ( Figure 9B); this can be reasonably ascribed to the presence of Pt nanoclusters which may induce disordered zones in the inverse opal structure and give rise to a different sensing mechanism at the microscale level.…”
Section: Preparation Of Precursorsmentioning
confidence: 86%
See 3 more Smart Citations
“…This is in agreement with the relatively regular array of WO 3 nanocrystals found in the inverse opal structure (see TEM micrographs, Figure 4a,b) and can be associated with a surface reactivity similar to that described for SnO 2 materials. 23 Differently, Pt-doped WO 3 sensors show β values as always higher than 0.5 ( Figure 9B); this can be reasonably ascribed to the presence of Pt nanoclusters which may induce disordered zones in the inverse opal structure and give rise to a different sensing mechanism at the microscale level.…”
Section: Preparation Of Precursorsmentioning
confidence: 86%
“…We also suggested that, in the presence of doping metal centers, the doping transition metal decreases its positive oxidation state by trapping the electrons given through reactions (6AÀ6C): 21,23 …”
Section: Preparation Of Precursorsmentioning
confidence: 97%
See 2 more Smart Citations
“…The mechanism of the metal-oxide sensors is based on the change of electrical conductance in response to the introduction of a small concentration of reducing gas, which reacts with the oxygen species at the oxide surface [1,4,5]. Many extensive studies, mainly concerning SnO 2 , widely investigate the dependence of the electrical response on both the electronic and morphological properties of the semiconductor [9][10][11][12][13][14][15]. The sensing mechanism towards different gases, H 2 [16], CO [17] and NO 2 [18] was also suggested.…”
Section: Introductionmentioning
confidence: 99%